2022
DOI: 10.1155/2022/3567879
|View full text |Cite
|
Sign up to set email alerts
|

Hydroalcoholic Leaf Extract of Isatis tinctoria L. via Antioxidative and Anti-Inflammatory Effects Reduces Stress-Induced Behavioral and Cellular Disorders in Mice

Abstract: Stress that can occur at different levels of a person’s life can cause and exacerbate various diseases. Oxidative stress and inflammation underlie this process at the cellular level. There is an urgent need to identify new and more effective therapeutic targets for the treatment of stress-induced behavioral disorders and specific drugs that affect these targets. Isatis tinctoria L. is a herbaceous species in the Brassicaceae family. Due to its potential antioxidant, nitric oxide- (NO-) inhibiting, anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…In chronic fatigue syndrome, depression and GAD, the neurotoxicity theories conceptualize that the effects of neuro-oxidative stress toxicity (OSTOX) coupled with lowered antioxidant (ANTIOX) defenses cause increased neurotoxicity leading to somatic and affective symptoms [ 30 , 31 ]. This is supported by translational data indicating that blocking nitro-oxidative stress, inflammatory and neurotoxic pathways with selective antioxidative compouds may alleviate depressive-, anxiety-, and chronic fatigue-like behaviors [ 25 , 26 , 30 , 35 40 ]. Moreover, in humans, treatment with selected antioxidants improves depression, anxiety and chronic fatigue symptoms [ 41 44 ].…”
Section: Introductionmentioning
confidence: 79%
“…In chronic fatigue syndrome, depression and GAD, the neurotoxicity theories conceptualize that the effects of neuro-oxidative stress toxicity (OSTOX) coupled with lowered antioxidant (ANTIOX) defenses cause increased neurotoxicity leading to somatic and affective symptoms [ 30 , 31 ]. This is supported by translational data indicating that blocking nitro-oxidative stress, inflammatory and neurotoxic pathways with selective antioxidative compouds may alleviate depressive-, anxiety-, and chronic fatigue-like behaviors [ 25 , 26 , 30 , 35 40 ]. Moreover, in humans, treatment with selected antioxidants improves depression, anxiety and chronic fatigue symptoms [ 41 44 ].…”
Section: Introductionmentioning
confidence: 79%
“…The target genes of differential transcripts are mainly enriched in immune regulatory functions, such as defense against viruses and immune responses. ISL has anti-inflammatory and antibacterial functions, and contains various antiviral substances, which can enhance the body's immunity and play an important role in regulating the health of fattening sheep ( 18 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ISL is rich in cellulose, which helps gastrointestinal peristalsis, promotes food digestion, increases satiety, and lowers cholesterol, reduces the accumulation of fat in the body. Research has found that the extract of ISL has multiple effects on inhibiting skin fibroblast aging by regulating mTOR-NF-κB-SASP signaling (17), reduces stress-induced behavior and cellular disorders in mice through antioxidant and antiinflammatory effects (18), and the extract also has anti-wrinkle Abbreviations: CON, basal diet; ISL, isatis leaf; DM, dry matter; CP, crude protein; NDF, neutral detergent fiber; ADF, acid detergent fiber; VFA, volatile fatty acid; UPLC-Q-TOF-MS, ultra-high-performance liquid chromatography-tandem quadrupole time-of-flight mass spectrometry; ADG, average daily gain; ADFI, average daily feed intake; VIP, variable projection importance; DEG, di erentially expressed gene; GO, Gene ontology; circRNA, circular RNA; lncRNA, long stranded non coding RNA; miRNA, MicroRNA; LPS, lipopolysaccharides. effects (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts of I. tinctoria have shown strong anti-inflammatory activity [151,152]. Also, the hydroalcoholic leaf extract of I. tinctoria was shown to possess anti-depressive properties and can reduce stressinduced behavioral disorders in mice [153], making qingdainone an interesting candidate ZINC000042890265 (disulfuretin), an aurone derivative, can be found in Cotinus coggygria (known as "smoke tree") [140,141]. Disulfuretin demonstrated strong antioxidative activity in a 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay with an IC 50 of 9.7 µg/mL [140].…”
Section: Provenance Of Potential Lead Compoundsmentioning
confidence: 99%